A content analysis of comments on articles describing homosexuality disclosure - Žardeckaitė-Matulaitienė, Kristina; Gaidytė, Viktorija (Psichologija, 2018)
Both researchers and society agree that those who decide to disclose their sexual orientation can find acceptance and even support in these experiences, while others are met with negative reactions, such as anger, rejection or bullying etc. There are lots of controversial studies about the differences in reactions to the coming out of homosexual men and women. It is agreed that these attitudes could be defined as multidimensional constructs comprised of cognitive, affective, and behavioral components. A content analysis of comments on articles describing coming out of homosexual individuals has not been yet performed in Lithuania. The aim of this study was to analyze the content of comments as reactions to the articles describing homosexuality disclosure in order to reveal the prevailing beliefs, emotions and behavioral reactions toward the disclosure of homosexuality and to compare any differences in responses while taking into account the sex of a disclosed person. A content analysis of 380 comments collected on the websites lrytas.lt and delfi.lt was carried out. The validity of the content categories was assessed with a second-rater procedure. The agreement percentage among the raters ranged from 84 to 100 and Cohen’s kappa from 0.42 to 1 throughout the categories. After the first evaluation of the content and after an objective selection of the comments for this research, 156 comments, which were suitable for further analysis, were selected. The analysis has shown that commentators tend to have negative perceptions regarding the disclosure of a homosexual individual’s sexual orientation. In the comments of the articles describing homosexuality disclosure, it was most often expressed that homosexuality is an unnatural thing or a perversion; that homosexual people should not disclose their sexual orientation; that homosexual people should not be allowed to raise children. At the same time, any positive attitude was expressed rarely. The most prevailing positive attitude is the following: homosexual people are just as normal as heterosexual people. Negative emotions, such as anger or disgust, as well as homophobic bullying (offensive remarks, jokes, and name-calling), were dominating in the comments. The accepting behavior (not encouraging someone to change), positive emotional reactions, such as support and suggestions to emigrate, were the rarest. The content analysis of the comments revealed the different reactions of the readers to homosexual men and women. The negative attitude toward raising children and the emotion of anger are more often addressed toward homosexual women than to homosexual men. The results of this study indicate the prevailing negative attitude toward the public disclosure of the sexual orientation of homosexual persons.
Keywords: homosexuality; disclosure; attitudes; content analysis